A Case Report of a Subdural Hematoma following Spinal Epidural prior to a Total Knee Arthroplasty - Brian J. Carlson; David G. Deckey; Henry D. Clarke; Joshua S. Bingham (Case Reports in Orthopedics)
Introduction. This case report adds to current literature on management of a subdural hematoma following total knee arthroplasty and is particularly important as joint replacement moves into outpatient surgery centers where the orthopedic surgery team becomes the sole patient contact point. Case Presentation. A 66-year-old male presented to the emergency department five days after elective robotic-assisted left total knee arthroplasty performed with spinal epidural with the symptoms of a persistent nonpostural headache. CT of the head revealed a small bifrontal acute subdural hematoma. He was admitted for overnight monitoring as a precaution. No vascular abnormalities or underlying pathology was found on further advanced imaging. He was discharged the following morning after follow-up CT showed no focal changes. Magnetic resonance imaging (MRI) one month later confirmed resolution of the subdural hematoma. Conclusion. Orthopedic surgeons should be aware of the signs and symptoms, as well as the risk factors for subdural hematomas following lumbar puncture, as it is a rare, but potentially life-threatening complication of spinal epidural.